Murine Q Fever Vaccination Model Reveals Sex Dimorphism in Early Phase Delayed-Type Hypersensitivity Responses - Binette, Picabo; Tesfamariam, Mahelat; Cockrell, Diane; Heinzen, Robert A.; Richards, Crystal; Shaia, Carl; Long, Carrie Mae (Frontiers in Immunology, 2022)
Delayed-type hypersensitivity (DTH) responses to microbial vaccines and related components are a major roadblock for widespread licensing of whole cell vaccines such as that of Q fever. Q fever is a zoonotic disease caused by the intracellular bacterium Coxiella burnetii. The only currently licensed vaccine, Q-Vax®, is a whole cell inactivated formulation that is associated with a potentially severe dermal post vaccination DTH response in previously sensitized individuals. To investigate the underlying immunologic mechanisms of this response and better represent the early-phase DTH response observed in humans, a murine sensitization and skin testing model was developed and employed. Female C57Bl/6J mice displayed the most robust early-phase DTH responses following sensitization and elicitation compared to their male counterparts and other mouse strains. Immunologic responses were measured within the skin, draining lymph nodes, and serum following both sensitization and elicitation with Q fever whole cell vaccines. Local immunologic responses in the dermis were characterized by inflammation primarily involving neutrophils, macrophages, and T cells. Secondary lymphoid organ profiling revealed distinct immunological signatures following both sensitization and elicitation with a sex-based dichotomy in T cell phenotypes and antigen presenting cell numbers. Beyond providing a post-Q fever vaccination DTH model that recapitulates early-phase DTH events, these data suggest that sex is a primary factor influencing the magnitude and composition of the ensuing response.